Judith of West Francia, Carolingian princess and first Countess of Flanders : biographical elements and legacy. - Vanderputten, Steven (Turnhout : Brepols, 2024)
Judith of West Francia is one of the most enigmatic of Charlemagne's early descendants. The daughter of the king of West Francia and future emperor Charles the Bald and his wife Ermentrude, she was one of only a handful of Carolingian princesses who were destined for marriage. Over the course of her teenage years she married two successive kings of Wessex, became the first consecrated queen of England, was widowed twice, returned to Francia with an immense dowry, and sparked a major diplomatic incident when she eloped with a nobleman from Flanders called Baldwin. Eventually she married Baldwin in early 864, and together they established the dynasty of the counts of Flanders. In doing so the couple laid the groundwork for what would become one of the mightiest and most prestigious territorial principalities in north-western Europe in the tenth and eleventh centuries. But even in the tenth century, exceedingly few written memories of Judith's life survived. This explains why she was never the subject of a biography in the medieval or early modern eras, and why scholarship's understanding of her life and legacy remains highly fragmented. This volume sets the record straight, offering an accessible and interdisciplinary discussion of all relevant and documented aspects of Judith's life and legacy.
boek